2021
DOI: 10.1021/acsanm.1c02227
|View full text |Cite
|
Sign up to set email alerts
|

Cross Disjoint Mortise Confined Solid-State Nanopores for Single-Molecule Detection

Abstract: Solid-state nanopores have attracted widespread attention in the singlemolecule detection application. However, getting controllable nanopores with high sensitivity and robustness requires a revolutionary breakthrough in nanopore fabrication. As a convenient and low-cost nanopore fabrication method, the controlled dielectric breakdown technology can hardly control the position and number of nanopores. This work proposes a concept of cross disjoint mortise confined solid-state nanopore (CDM-Nanopore) fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Recently, Wang’s group demonstrated that the applied voltage can be controlled across different membranes and generate nanopores at a specific position in the flow system [ 155 , 156 , 197 ]. They also reported that CBD nanopores formed in a localized manner at the cross-disjoint mortise structures generated by Ga-FIB etching [ 198 ].…”
Section: Localized Nanopore Fabrication By Cbdmentioning
confidence: 99%
“…Recently, Wang’s group demonstrated that the applied voltage can be controlled across different membranes and generate nanopores at a specific position in the flow system [ 155 , 156 , 197 ]. They also reported that CBD nanopores formed in a localized manner at the cross-disjoint mortise structures generated by Ga-FIB etching [ 198 ].…”
Section: Localized Nanopore Fabrication By Cbdmentioning
confidence: 99%
“…They are highly tunable in geometry and surface properties and thus enable novel applications. Examples include filtration of water to remove contaminants such as oil and dyes, nanopore sensors for single molecules, proteins, blood sugar, and drugs as well as DNA, ssDNA, and protein sequencing . The potential of using nanofluidic devices based on nanopore membranes for novel applications such as power generation and electroosmotic pumps has also been explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The zero-depth interfacial nanopore was formed by etching two overlapping metal nanorods in a polymer plate, demonstrating excellent mechanical properties and low noise levels . In our previous research, based on the zero-depth interfacial nanopores, we proposed a cross-disjoint mortise-confined solid-state nanopore (CDM nanopore, Figure ), fabricated by using a gallium focus ion beam and controlled dielectric breakdown technologies . The long-term molecular detection experiments have also preliminarily demonstrated the robustness and low noise characteristics of the CDM nanopore .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, based on the zero-depth interfacial nanopores, we proposed a cross-disjoint mortise-confined solid-state nanopore (CDM nanopore, Figure ), fabricated by using a gallium focus ion beam and controlled dielectric breakdown technologies . The long-term molecular detection experiments have also preliminarily demonstrated the robustness and low noise characteristics of the CDM nanopore . In order to extend the application of CDM nanopores to DNA/RNA sequencing, high spatial resolution in CDM nanopores must be obtained.…”
Section: Introductionmentioning
confidence: 99%